Dampak Modal Kerja dan Aktiva Tetap Terhadap Laba dengan Pendapatan Sebagai Intervening Pada Perusahaan BUMN di BEI - Windreis, Christ (TIN: Terapan Informatika Nusantara, 2021)
The purpose of this study was to determine the effect of working capital on net income in BUMN companies on the IDX, to determine the effect of fixed assets on net income in BUMN companies on the IDX, to determine the effect of working capital on earnings in BUMN companies on the IDX, to determine the effect of assets on the IDX. Fixed assets on income in BUMN companies on the IDX, to determine the effect of working capital on net income through income in BUMN companies on the IDX, to determine the effect of fixed assets on net income through income in BUMN companies on the IDX, and to determine the effect of income on net income on the IDX. state-owned companies on the IDX. The results of the study are that working capital has no effect on net income in BUMN companies on the IDX, fixed assets have an effect on net income in BUMN companies on the IDX, working capital has no effect on income, fixed assets affect earnings on BUMN companies on the IDX, working capital has no effect on net income through income in state-owned companies on the IDX, fixed assets affect net income through income on state-owned companies on the IDX, income affects net income on state-owned companies on the IDX